2019
DOI: 10.1107/s1600577518015370
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of propagating and standing surface acoustic waves by stroboscopic X-ray photoemission electron microscopy

Abstract: The quantification of surface acoustic waves (SAWs) in LiNbO3 piezoelectric crystals by stroboscopic X‐ray photoemission electron microscopy (XPEEM), with a temporal smearing below 80 ps and a spatial resolution below 100 nm, is reported. The contrast mechanism is the varying piezoelectric surface potential associated with the SAW phase. Thus, kinetic energy spectra of photoemitted secondary electrons measure directly the SAW electrical amplitude and allow for the quantification of the associated strain. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 20 publications
0
17
0
3
Order By: Relevance
“…On the free LiNbO 3 surface the SAWs are readily visible in PEEM because,being an insulating piezoelectric material, the acoustic waves are accompanied by av ariation of the surface potential of up to 3Vamplitude. [15] Collecting stroboscopic images with 2nsseparation, the propagating SAWs are directly imaged on the uncovered LiNbO 3 ,a ss hown at the bottom of Figure 2a.F or as ingle stroboscopic image,l ong integration times can be used because between two synchrotron light pulses,t he synchronized SAWadvances by exactly one wavelength, overlaying multiple identical partial images on the detector.I nc ontrast, on the Pt film, the variations in the LiNbO 3 surface potential are completely shielded by the equipotential metal surface (for details on the electrical characterization and film morphology please refer to the supplementary information).…”
Section: Saw-induced Work Function Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the free LiNbO 3 surface the SAWs are readily visible in PEEM because,being an insulating piezoelectric material, the acoustic waves are accompanied by av ariation of the surface potential of up to 3Vamplitude. [15] Collecting stroboscopic images with 2nsseparation, the propagating SAWs are directly imaged on the uncovered LiNbO 3 ,a ss hown at the bottom of Figure 2a.F or as ingle stroboscopic image,l ong integration times can be used because between two synchrotron light pulses,t he synchronized SAWadvances by exactly one wavelength, overlaying multiple identical partial images on the detector.I nc ontrast, on the Pt film, the variations in the LiNbO 3 surface potential are completely shielded by the equipotential metal surface (for details on the electrical characterization and film morphology please refer to the supplementary information).…”
Section: Saw-induced Work Function Changesmentioning
confidence: 99%
“…[3] This delayed response is also observed in UHV-type experiments on Pt(110), where transport limitations play no role.T his unsolved question was the primary motivation for us to look into the mechanism of catalytic promotion by SAWs in asystematic manner.Besides an electronic effect, SAWmight also induce changes in the arrangement of surface atoms,i.e. cause surface restructuring,which could enhance the catalytic activity.W ea ssess the electronic effects by taking advantage of the time structure of synchrotron radiation that allows us to take stroboscopic photoelectron emission images of the waves with at ime resolution below 100 ps, [15] and thus detect changes in the local WF as af unction of the SAWp hase. Fort he detection of restructuring effects,w ed esigned abimetallic model catalyst with avertically layered structure that enables measuring vertical intermixing induced by SAWs.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, experiments employ an optical laser pulse which is diffracted from the excited modes via photothermal or photoelastic effects [28,29]. Alternatively, PSDs can be detected using x-ray diffraction and photoemission electron microscopy techniques [30][31][32]. We have recently shown that the PSD associated with the excited quasi-static and transient modes may also be probed by TR-XRR [14,15].…”
Section: Coherent Control Of Periodic Surface Deformationsmentioning
confidence: 99%
“…Diese ungelçste Frage war füruns die Hauptmotivation, den Mechanismus der katalytischen Promotion durch SAWs systematisch zu untersuchen. Neben einem elektronischen Effekt kçnnten die SAWs auch ¾nderungen in der Anordnung der Oberflächenatome,d .h.e ine Oberflächenumstrukturierung,i nduzieren, welche die katalytische Aktivitätv erstärken kçnnte.W ir quantifizieren die durch SAWs hervorgerufenen elektronischen Effekte,i ndem wir uns die Zeitstruktur der Synchrotronstrahlung zunutze machen, die es uns erlaubt, stroboskopische Photoelektronenemissionsbilder der Oberflächenwellen mit einer zeitlichen Auflçsung unter 100 ps aufzunehmen, [15] und so Veränderungen in der lokalen WF in Abhängigkeit von der SAW-Phase zu messen. Fürd ie Detektion von Umstrukturierungseffekten haben wir einen Bimetall-Modellkatalysator mit vertikal geschichteter Struktur entwickelt, der die Messung der durch SAWs induzierten vertikalen Diffusion ermçglicht.…”
Section: Introductionunclassified